Pediatric Cervical Spine Instrumentation: Current Concept Review: From the Cervical Spine Interest Group of the Pediatric Spine Study Group (PSSG) - Bauer, Jennifer M.; Brockmeyer, Douglas L.; Pahys, Josh M.; Yaszay, Burt; Hedequist, Daniel J. (Journal of the Pediatric Orthopaedic Society of North America, 2021)
Pediatric cervical spine fixation can be challenging to place as it must accommodate small and often abnormal anatomy. However, multiple safe options exist. Halo-vest orthosis is a useful adjuvant technique to modern rigid implants. Occipital plates, C1 lateral mass screws, multiple C2 trajectories, and subaxial lateral mass screws all have proven efficacy in young children. Anterior approach for decompression and anterior column support is possible, with creative implant and graft solutions in the smallest children. While complications are reported, modern rigid implants can be used safely in pediatric spine with careful pre-operative anatomic understanding and planning.